Posttransurethral Resection of Prostate Recurrent Life Threatening Hematuria: A Rare Cause - MC Arya; Lalit Kumar; Ruchi Mittal; Rajeev Kumar; Mayank Baid (Case Reports in Urology)
Herein, we present a case report of post-TURP (transurethral resection of prostate) recurrent severe hematuria due to right internal iliac artery pseudoaneurysm protruding into bladder lumen. A 60-year-old male presented with recurrent massive hematuria following TURP done elsewhere 15 days before. His hemoglobin was 4 gm/dL after 13 units of blood transfusion and repeated clot evacuations. His blood urea, serum creatinine, and coagulation profile studies were normal. Ultrasonography of abdomen showed multiple clots in the bladder. Cystoscopy revealed clots with a right posterolateral wall unhealthy area. After stabilizing the patient, contrast enhanced CT urography revealed intravesical aneurysm. CT angiography showed pseudoaneurysm of a branch of internal iliac artery protruding into urinary bladder lumen. We referred patient to selective embolization of the lesion but the procedure was unsuccessful. At last, ipsilateral internal iliac artery ligation relieved hematuria. But on postoperative day 2, patient suddenly collapsed and deceased, presumably due to cardiomorbidities.